Фотоелектричні властивості структур кристалічного кремнію з гідрогенізованими нанорозмірними вкрапленнями - Бабиченко, О. Ю. (ХНУРЕ, 2019)
Дисертаційну роботу присвячено отриманню властивостей гетероморфних напівпровідникових матеріалів на основі кристалічного та аморфного кремнію різного виду та ступеня аморфізації, суттєвих з точки зору застосування їх у фотоелектричних перетворювачах для сонячної енергетики. Отримано розподіл щільності електронних станів та спектр нормованої узагальненої функції розподілу щільності станів в гетероморфному кремнії з урахуванням ступеня розупорядкованості структури, розмірів та морфології включень. Одержані характеристики фотопровідності гетероструктури аморфного гідрогенізованого та монокристалічного кремнію як функції розмірів та морфології аморфних включень в кристалічному субстраті дозволили визначити основні шляхи підвищення ефективності сонячних елементів. Отримали подальший розвиток методи розрахунку впливу аморфних неоднорідностей на фотопровідність кристалічного кремнію в залежності від фізичних властивостей і геометрії цих неоднорідностей, що дозволило поглибити уявлення про фізичні процеси в гетероструктурах типу аморфний/кристалічний кремній. The dissertation is devoted to obtaining properties of heteromorphic semiconductormaterials based on crystalline and amorphous silicon of various kind and degree of amorphization essential from the point of view of their use in photoelectric converters for solar energetics. The dissertation contains the following new scientific results: 1. For the first time, the electron density states distribution and the spectrum of the normalized generalized function of the density states distribution in the heteromorphic silicon are obtained in a theoretical way, considering the degree of structure disorder, the size and morphology of the inclusions. 2. The obtained photoconductivity characteristics of the heterostructure of amorphous hydrogenated and single-crystalline silicon, as functions of the size and morphology of amorphous inclusions in the crystalline substrate, make it possible to determine the main ways of increasing the efficiency of solar cells. 3. Methods of calculating the influence of amorphous inhomogeneities on the photoconductivity of crystalline silicon are more developed, depending on the physical properties and geometry of these inhomogeneities; this allows to deepen the understanding of physical processes in amorphous/crystalline silicon heterostructures. The reliability of the theoretical studies performed in the work is substantiated by the physical correctness of the applied modeling approaches and agreement of their results with known results of experimental researches. The influence of the degree of disordering of amorphous semiconductor structure on the function of state density distribution and interconnections of structure-dependent properties of semiconductors, specifically, optical and electronic ones, has been revealed; this creates the basis of production technologies for new semiconductor materials with predetermined properties. The technique developed to determine the dependence of the influence of amorphous inhomogeneities on the photoconductivity of crystalline silicon on the physical properties and geometry of these inhomogeneities is a theoretical basis for the design of energy efficient solar cells of the next generation. The results of the work are used in the educational process of higher education institutions for studying the principles of a new perspective class of photoelectric converters based on modified semiconductor materials.
Keywords: аморфний гідрогенізований кремній; кристалічний кремній; зони розупорядкованості; аморфні вкраплення; сонячні елементи; фотогенерація; гетероструктура; фотоперетворювач; amorphous hydrogenated silicon; disordered zones; amorphous inclusions; solar cells; photogeneration; heterostructure; photoconverter